The role of the legislative branch in the development of educational public policies - Cardoso, Paulo Vinícius Rivas; Souza, Kellcia Rezende (Revista Hipótese, 2025)
The objective of this article is to present a bibliographic review on the role of the Legislative Branch in the development of educational policies in Brazilian scientific productions from 2007 to 2024. To this end, it analyzes research made available in the Brazilian Digital Library of Theses and Dissertations during the specified period. From the analysis, six studies were identified: four master’s dissertations—three in the field of education and one in public administration—and two doctoral theses in the field of education. It can be concluded that a low number of compatible references were found, demonstrating that, despite its importance in enhancing educational public policy, the field has still been approached in a limited manner. There was no observed evaluation of the role of the legislative branch in the construction of educational agendas, the definition of public problems in education, or the oversight of the efficiency of already implemented policies. This gap underestimates the importance of the legislative branch in shaping public policies and highlights the need for a detailed approach to understanding its influence and contribution.